Factors Influencing Obesity Levels in Productive Age 20-24 Years Old in Africa - Ridla, Akhmad Zainur; Nofiyanti, Elisa Putri; Kartikasari, Oktaviana Dwi; Nurrohmah, Setyowati; Putri, Reza Lailiyatul; Adjie, Ra’uuf Thrisna; Nurhidayah, Ririn; Pasaribu, Indah Octavia Br (Jurnal Kesehatan Komunitas Indonesia, 2023)
Obesity is one of the considerable medical issues happening all around the world. Obesity has a high rate that makes it one of the reasons for difficulties in adults. People with excess weight should maintain a healthy diet to avoid diseases caused by high obesity. This research analyzes obesity rates in the productive age scope of 20-24 years in 3 nations on the African landmass (Gambia, Cameroon, and Ethiopia) utilizing information from the Demographic and Health Surveys (DHS) platform from 2018 to 2020. The strategy used to process the data is logistic regression analysis. In this review, four factors are utilized, including living environment, education level of abundance in metropolitan/provincial regions, and occupation. The statistical analysis used here is logistic regression linked to the IBM SPSS Statistic 25 application to identify the factors associated with the Prevalence of obesity in the three countries sampled in the study. From the study results, the Prevalence of obesity in Cameroon country is 14.7%, in the Gambia is 10.8%, and in Ethiopia is 4.4%. From the statistical test using logistic regression, the odds ratio (OR)> 1 means a relationship between these four risk factors and the occurrence of obesity in the 3 sample countries. This study concludes that residence, level of education, wealth index, and work activities directly affect a person's nutritional status, causing obesity.